PERANCANGAN WISATA EDUKASI PETERNAKAN SAPI DI BOGOR DENGAN PENDEKATAN ARSITEKTUR RAMAH LINGKUNGAN - Arindya Rahmah Jaya W; Karya Subagya (MAESTRO, 2019)
Cattle farming is a breeding activity and cultivating livestock to get the benefits and results of these activities. Cages have two types, namely individuals and groups. Tourism Education is a tourist trip that has added educational value, not just traveling, but also aims to add values to education or education for all participants. Educational tourism is an activity that is generally carried out by educational institutions, such as schools and family groups. Environmentally friendly architecture, also a green architecture, includes harmony between humans and their natural environment. Green architecture also contains other dimensions such as time, natural environment, socio-cultural, space, and building techniques. This shows that green architecture is complex, dense and vital compared to architecture in general.